2020
DOI: 10.1080/2162402x.2020.1773200
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative potential and response to nivolumab in clear cell renal cell carcinoma patients

Abstract: Background: Biomarkers predicting immunotherapy response in metastatic renal cell cancer (mRCC) are lacking. PD-L1 immunohistochemistry is a complementary diagnostic for immune checkpoint inhibitors (ICIs) in mRCC, but has shown minimal clinical utility and is not used in routine clinical practice. Methods: Tumor specimens from 56 patients with mRCC who received nivolumab were evaluated for PD-L1, cell proliferation (targeted RNA-seq), and outcome. Results: For 56 patients treated with nivolumab as a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A recent study on clear cell renal carcinoma treated with nivolumab identified the proliferative ability, measured by the mean expression rank value of 10 proliferation related genes, as a response predictor in these patients. Patients with a lower proliferation rate had poorer responses [ 28 ]. Furthermore, a recent phase II basket trial of dual blockade with ipilimumab (anti-CTLA4) and nivolumab (anti-PD1) in nonpancreatic neuroendocrine tumors showed an impressive 44% response rate (8 out of 18 patients) in high grade tumors versus 0% (0 out of 14 patients) in low or intermediate grade tumors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on clear cell renal carcinoma treated with nivolumab identified the proliferative ability, measured by the mean expression rank value of 10 proliferation related genes, as a response predictor in these patients. Patients with a lower proliferation rate had poorer responses [ 28 ]. Furthermore, a recent phase II basket trial of dual blockade with ipilimumab (anti-CTLA4) and nivolumab (anti-PD1) in nonpancreatic neuroendocrine tumors showed an impressive 44% response rate (8 out of 18 patients) in high grade tumors versus 0% (0 out of 14 patients) in low or intermediate grade tumors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the disadvantages of these prevalent biomarkers suggested that novel robust biomarkers are needed. A previous study found that 10 cell proliferation genes, including BUB1, CCNB2, and CDK1, could act as indicators for response to immune checkpoint inhibitors in PD-L1 negative renal cell carcinoma [ 43 ]. In the present study, the six hub proteins were found to be negatively correlated with most immune cell types such as CD4 T cell, B cell, and CD8 T cell ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients, several factors work together to result in T-cell dysfunction, ultimately leading to an exhausted T-cell phenotype [20]. Our previous work in a metastatic GEAC population showed that overweight individuals (BMI ≥ 25) were more likely to express PD-L1 in their TME than normal-weight individuals [21]. In addition, many other immune suppressive markers, such as FOXP3 and IDO1, were found to be upregulated in the obese group.…”
Section: Discussionmentioning
confidence: 97%